The science and engineering of materials : 7th edition - Askeland, R. Donald. (Cengage Learning, 2014)
This updated Seventh Edition of The Science And Engineering Of Materials helps you to develop an understanding of the relationship between structure, processing, and properties of materials. Because the book has more material than is needed for a one-semester course, you will also have a useful reference for subsequent courses in manufacturing, materials, design, or materials selection. The Askeland text emphasizes a science-based approach to materials engineering that highlights how the structure of materials at various length scales gives rise to materials properties. This connection between structure and properties is key to innovating with materials, both in the synthesis of new materials and enabling new applications with existing materials. The science-based approach highlights how materials change with time and due to loading and environment - a key concept that is often overlooked when using charts and databases to select materials.